Functional near-infrared spectroscopy in the assessment of rehabilitation efficacy of virtual reality products for people with cognitive disorders - Qu, Jing; Zhang, Yanjie; Bu, Lingguo (International journal of industrial ergonomics, 2023)
Rehabilitation products for people with cognitive disorders (CDs) have gained increasing attention due to the aging population. However, existing approaches to rehabilitation product design do not adequately consider the importance of feedback information. To address this issue, two VR products with different roaming environments were developed, and 30 elderly participants completed an ergonomic experiment while objective user physiological data were continuously collected using functional near-infrared spectroscopy (fNIRS). The shifts in the subjects’ brain function were analyzed from brain activation and effective connectivity perspectives. Results indicated that VR stimulates various brain areas, with an immersive interactive environment the main influencing factor. There were notable variations in how different virtual settings stimulated individual brain functions. Environmental variables should be included in selecting rehabilitation product design theories. This study provides a quantitative assessment of product ergonomic design for the CDs population and offers guidance in the design of rehabilitation products. This study developed VR rehabilitation products for cognitive disorders based on data-driven product design. Brain function data were introduced to propose a quantitative assessment method for the rehabilitation efficacy of VR products. VR product design is a hot issue in the industry. Evaluating the efficiency of VR products is an urgent challenge for the industry. •Quantitative evaluation of product efficacy using functional near-infrared spectroscopy.•A quantitative assessment method based on the two indicators of wavelet amplitude and granger causality is proposed.•The immersive and interactive experience provided by VR may be the main cause of functional changes in visual-related brain areas.•Suggests the inclusion of environmental variables in the selection of product design theories for rehabilitation.